Front Cover: H‐Mediated Magnetic Interactions between Layers in a 2D MnII–Dicyanamide Polymer: Neutron Diffraction, DFT, and Quantum Monte Carlo Calculations (Eur. J. Inorg. Chem. 3‐4/2018). Issue 3 (15th January 2018) - Gillon, Béatrice; Hammerschmied, Albert; Gukasov, Arsen; Cousson, Alain; Cauchy, Thomas; Ruiz, Eliseo; Schlueter, John A.; Manson, Jamie L.
Abstract : The Front Cover shows the magnetic phase diagram of the quasi 2D compound Mn II (dca)2 (pym)(H2 O) established by neutron diffraction on the 5C1 diffractometer at LLB‐Orphée. The directions of the ordered Mn II magnetic moments in the antiferromagnetic phases AF1 and AF2 are displayed for two neighboring layers. The induced spin densities (positive in red, negative in blue), determined by polarized neutron diffraction in the paramagnetic phase, depict the different magnetic interaction pathways: magnetic coupling is mediated by dca bridges inside layers and by H bonding between layers. More information can be found in theFull Paper by B. Gillon, J. L. Manson et al. For more on the story behind the cover research, see theCover Profile .